XANES Investigations on Electronic Structure and Magnetic Properties of GaFeO3 Nanocrystals - Sharma, Aditya; Varshney, Mayora; Gautam, Tanisha; Sharma, Anjali; Vij, Ankush; Sharma, Ram K.; Lee, Byeong-hyeon; Chae, Keun Hwa; Won, Sung Ok (Institute of Electrical and Electronics Engineers, 2022)
Nanocrystals of GaFeO3 were prepared using co-precipitation followed by thermal annealing at 800 degrees C for 6 h. The lattice parameters and crystallite size were studied using x-ray diffraction (XRD). Transmission electron microscopy (TEM) measurements were performed to study the size and morphology and revealed the formation of 40-70 nm sized nanoparticles. X-ray absorption near-edge structure measurement was performed to probe the valence state of constituent elements in the GaFeO 3 nanocrystals. It has been observed that Fe is present in solely the +3 valence state (i.e., Fe3+). The Ga3+ ions are found with vivid distribution at tetrahedral and octahedral sites and the occupancy of Ga3+ ions is quantitatively evaluated using Ga K-edge XANES spectra. The low-temperature (50 K) M-H loop measurement conveys a ferrimagnetic character of GaFeO3 compound. The paramagnetic behavior is seen at 300 K. The observed magnetic moments per formula unit (similar to 1.6 mu(B)) are close to the magnetic moment of Fe3+ ions with a low spin state (t(2g)(5)). The abundant Ga3+ ions at the tetrahedral site, as confirmed by Ga K-edge XANES analysis, lead to weak anisotropy in the compound and favor the regular hysteresis loop rather the pinched-like hysteresis loop at 50 K.